The History of International Rankings and The Present Impact on Students’ Education - Roxana - Adriana PUIU (MECHNO); Gabriel PETREA; Cristian - Vasile DOICIN (Communications of International Proceedings, 2022)
For over a decade, global university rankings have played an important role in increasing status competitiveness in higher education. As competition for prestige in an interconnected world became more central not only to universities and national education systems but also to nation-states, the pressures either to succeed in existing hierarchies or to meet the rules of hierarchies became two main strategies. Thus, most universities try to adapt to the existing hierarchies.
Keywords: Ranking; International; Higher Education; Research; Students.